Implementation of Autocad® Civil 3D for Cut and Fill Calculation of Margoyoso Road Section BTS, Jepara – Kudus Regency - Susanty Handayani; Dea Rizkylia Kusumaningrum; Jody Martin Ginting (Fakultas Teknik Sipil dan Perencanaan, 2025)
The small and medium-sized industry in Jepara Regency has shown significant progress, with one of the most notable small industries in Margoyoso Village being the monel craft industry. Good infrastructure support, such as Margoyoso Road, undoubtedly contributes to the local economy. One indicator of good infrastructure development is efficiency in terms of time and cost. This paper discusses the implementation of AutoCAD® Civil 3D in cut-and-fill calculations. The calculation process using AutoCAD® Civil 3D with the cross-section method resulted in a cut volume of 57,581.60 m^3, a fill volume of 31,952.90 m^3, and a net volume of 25,628.70 m^3. These results prove that the implementation of AutoCAD® Civil 3D provides faster, more accurate, and more precise data.